Clinical Laboratory and Molecular Detection of Extended Spectrum beta lactamases: A Review Update - Rahman, Mostaqimur; Rahman, M. Mujibur; Jahan, Waseka Akhter (Bangladesh Journal of Infectious Diseases, 2015)
Extended Spectrum ?-lactamases (ESBLs) can confer resistance to all extended spectrum cephalosporins, all penicillins and monobactam. Being plasmid and transposon mediated has facilitated the spread of these enzymes to other species of bacteria. This is a challenge for the laboratory to detect ESBL-containing Gramnegative bacilli because they can appear susceptible in vitro to certain beta-lactam antimicrobial agents yet result in clinical treatment failure. Till now there is no gold standard test for detection of ESBLs. CLSI recommended the phenotypic method as confirmatory test. However, the traditional methods need much labor and time for cultivation and require at least overnight incubation after isolated colonies are available from primary culture. Therefore, about 48 hours is required for ESBLs reporting by traditional methods. Molecular characterization of the isolated ESBL was also not possible in maximum laboratories due to lack of facilities. But rapid detection of ESBLs from the patient with severe infection is urgently required; otherwise it may be fatal. In this present review this diagnostic dilemma of ESBL has been discussed. Bangladesh J Infect Dis 2014;1(1):12-17<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />